Mortality reduction with 23-valent pneumococcal polysaccharide vaccine: a systematic review and meta-analysis - Muhammed Shabil; Shilpa Gaidhane; Suhas Ballal; Sanjay Kumar; Mahakshit Bhat; Shilpa Sharma; M. Ravi Kumar; Sarvesh Rustagi; Mahalaqua Nazli Khatib; Nishant Rai; Sanjit Sah; Edward Mawejje; et al. (Pneumonia)
Abstract Background Pneumococcal disease, caused by Streptococcus pneumoniae, imposes a significant global health burden, particularly affecting vulnerable groups such as the elderly and immunocompromised. The 23-valent pneumococcal polysaccharide vaccine (PPV23) is designed to protect against 23 serotypes of Streptococcus pneumoniae. However, there is ongoing debate about its effectiveness in reducing all-cause mortality. This systematic review and meta-analysis aimed to evaluate the efficacy of PPV23 in reducing all-cause and pneumonia-related mortality among adults. Methods A systematic search was conducted across PubMed, Embase, and Web of Science, focusing on studies that evaluated the mortality outcomes of adults vaccinated with PPV23 compared to non-vaccinated adults. Both randomized controlled trials (RCTs) and observational studies were included, while case reports, case series, and non-human studies were excluded. Data extraction and quality assessment were facilitated by Nested Knowledge software, using the Newcastle-Ottawa Scale for observational studies and the Cochrane Risk of Bias tool for RCTs. Results The search yielded 826 records, with 19 studies meeting the inclusion criteria. The pooled analysis of four RCTs showed no significant reduction in all-cause mortality (RR = 1.030; 95% CI: 0.945, 1.122). However, analysis of pneumonia-related mortality across various studies indicated a significant reduction (HR = 0.504; 95% CI: 0.316, 0.693). Moderate to high heterogeneity was noted in mortality studies, and a potential publication bias was identified. Conclusion The findings suggest that while PPV23 may not significantly reduce all-cause mortality, it is effective in reducing pneumonia-related mortality among adults, particularly in those at higher risk. These results support the continued use of PPV23 in targeted adult populations, emphasizing the need for more primary studies to explore its effectiveness across diverse groups.